THE EFFECT OF COST OF GOODS SOLD ON NET PROFIT IN BASIC INDUSTRIAL AND CHEMICAL MANUFACTURING COMPANIES LISTED ON THE IDX - Esra Supriyani; Lorina Siregar Sudjiman (Jurnal Scientia, 2023)
Problem faced by researcher include: 1) How much cost of goods sold growth in basic and chemical industrial companies listed on IDX in 2020-2021? 2) How much is the growth of net profit in basic and chemical industrial companies listed on IDX in 2020-2021? 3) How much influence cost of gods sold on net income in the basic and chemical industry in 2020-2021? With the aim of knowing and analyzing 1) The magnitude of the development of the main costs in basic and chemical industry companies listed on IDX in 2020-2021 2) The amount of development of net profit in basic and chemical industry companies listed in IDX in 2020-2021? 3) The magnitude of the effect of the cost of goods sold on net profit in the basic and chemical industry in 2020-2021? This study used secondary data processed by researchers and taken from the financial statements of basic and chemical industry companies in 20, 20-20, 21. The population showed that there were 75 basic and chemical industry companies listed on the IDX. Sample determination used purposive sampling and found 45 companies whose 90 data can be used for processing and analysis. The processed data are quantitative data analyzed by causal associations. The results showed that the: 1) cost of gods sold experienced an average increase of 21% with the highest increase of 79% in the company Mark's code and decrease in the cost of goods sales of -12% in the BTON code company. 2) Net profit experienced an average increase of 334% with the highest increase of 8,351% in the CAKK code company while a decrease in net profit was -65% in the ESIP code company. 3) Partially the cost of goods sold has a positive and significantly strong effect on net profit in basic and chemical industry companies in 2020-2021.